THE CORRELATION BETWEEN STUDENTS’ MOTIVATION IN LEARNING ENGLISH AND THEIR WRITING ABILITY IN DESCRIPTIVE TEXT AT THE EIGHTH GRADE OF MTsN 01 LAMPUNG UTARA ACADEMIC YEAR 2022/2023 - Ranti Melia Sari; Badawi; Dewi Sartipa; Shela Munica Putri; Angga Kurniawan; Anisa Permata Sari; Aprilia Kartika; Veronika Veninda (Edukasi Lingua Sastra, 2023)
English is one of the most commonly used as a language of communication of people from different country. In learning English there are some skills that should be mastered by the students, one of them is writing descriptive text. Descriptive text is kind of text that the main idea is delivered by describing in detail object, place, or events for the readers. The students are expected to be able mastery writing skill. But in fact, there are many students still feel difficult in writing correctly.The strategy can be done by the teacher or the students themselves to increase student motivation. Motivation is a term that is already common in regular speech to encourage individual or a group students to take an active role in their studies or employment in learning english specifcally descriptive text. The problem in this research is students feel writing descriptve text and lack of student’s learning motvatiion in writing descriptive text . objective of the research is conducted to find out whether there is significant correlation between students’ motivation in learning English and their writing ability in descriptive text at the eighth grade of MTsN 01 North Lampung. This research used correlational research. Simple random sampling technique was applied to select the sample. Population of this research was eighth grade at MTsN 01 North Lampung which consist of 211 students. The total sample of this research was 37 students. The research instrument used to collect the data were questionnaire and writing test. There are 29 valid items. Value of reliability in questionnaire rcount was greater than rtable (0,84 > 0,329) and Value of reliability in writing test . In analyzing the data 0,830. the researcher was used Pearson Product Moment formula. The result of this research showed that Ha is accepted with the result of hypothesis test rcount is higher than rtable which is 0,421 > 0,325. furthermore, the result of t-test was tcount is higher than ttable which is 2.98 ˃ 2.03, it means that there is significant correlation between students’ motivation and their writing ability descriptive text at the eighth grade of MTsN 01 North Lampung academic year 2022/2023.